Development Strategy for Micro, Small, and Medium Enterprises through Islamic Financial Inclusion - Novatul Isrowiyah; Warno Warno; Rahman El Junusi (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
This study calculates and analyzes the Islamic financial inclusion index which covers three dimensions; accessibility, availability, and usage of sharia banking. The results showed that the level of Islamic financial inclusion in Indonesia was classified as low during the study period and DKI Jakarta Province was the most inclusive province in Indonesia. Furthermore, this study analyzes the effect of the Islamic financial inclusion index on Islamic financing channeled to Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Using the saturated sampling method, a total of 33 provinces in Indonesia were selected as samples with an observation period. The results show that the Islamic Financial Inclusion Index (IIK) has a significant positive effect on sharia financing channeled to the MSME sector, one of the regions that appears to be growing faster than other regions is Aceh. This research is different from previous financial sector inclusiveness studies that still see and study conventional (non-sharia) financial inclusion and find out the impact of sharia financial inclusion based on sharia financial inclusion indexes on sharia financing distributed to Micro, Small and Medium Enterprises in Indonesia and discuss comprehensively for MSME.